Hollow Micro-/Nanostructure Reviving Lithium-sulfur Batteries - Zhao, Jilu; Yang, Mei; Yang, Nailiang; Wang, Jiangyan; Wang, Dan (Chemical research in Chinese universities, 2020)
High-energy-density lithium-sulfur(Li-S) batteries are drawing dramatic research interests to fulfill the ever-increasing demands of electrical vehicles. However, challenges with the insulating property of sulfur and its lithiation products and its large volume expansion, and the shuttle effect of lithium polysulfides, hinder the commercial application of Li-S batteries. Lots of material design concepts have been developed to address the failure modes. Among them, hollow micro-/nanostructures with abundant compositional and geometrical feasibility have been proved fruitful in addressing the current obstacles of Li-S batteries. Here, typical examples of designing hollow micro-/nanostructures to address the problems of Li-S batteries and simultaneously improve the practical capacity and lifespan are highlighted. In particular, the great effect of structural engineering on minimizing volume change, inhibiting the shuttle effect and catalyzing polysulfide conversion are discussed systematically. Finally, future directions of hollow nanostructure design to enhance the progress of Li-S batteries are also provided.